Ceramic orbital implant: a study of the efficacy, acceptability and safety of a locally produced hydroxyapatite orbital implant for the anophthalmic socket - Levitz, Mark Lewis (My University, 2008)
ABSTRACT A novel locally manufactured and developed porous hydroxyapatite orbital implant has been investigated and found to be as safe as commercially available implants. Objective To describe and analyze the results of twenty orbital implants implanted into patients in one arm of a multicentre trial. Methods A porous hydroxyapatite orbital implant with a smooth cap was developed and implanted into twenty patients. These patients were followed up for a period of four months. Patients were examined for signs of infection or extrusion of the implants. The amount of post-operative pain, chemosis, granuloma formation and vascularity was also assessed. Results None of the twenty patients had any signs of extrusion or infection at the termination of the study. There was very little pain or chemosis noted and no granuloma formation. Conclusion The locally developed implants were safe in anophthalmic eyes when reviewed after a four month follow-up period.
Keywords: orbital implant; hydroxyapatite